Production of Taq I restriction and modification enzymes by using two different expression systems - Toksoy, Ebru. (Thesis (Ph.D)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 2000, 2000)
Taq I restriction-modification system has been cloned and expressed using two different expression systems. In the first system, Taq I restriction endonuclease was expressed as a fusion protein with the maltose-binding protein. Although the MBP-Taq I fusion protein was targeted to the periplasmic space, 80-90 per cent of Taq I endonuclease activity was found to be excreted to the growth medium without cell lysis. The fusion protein was also purified via amylose affinity chromatography from the cytoplasm, periplasm and medium of recombinant E. coli cells. Co-expression of the Taq I methylase gene improved the plasmid stability and the periplasmic and extracellular transport of the fusion protein under controlled bioreactor conditions resulting in 0.6x106 U/L extracellular Taq I endonuclease activity yield in E. coli XL1(pH185, pETMET) culture. For the second system, Taq I endonuclease gene was expressed under the control of the T7 RNA polymerase promoter. Growth and enzyme productivity of the unprotected and methylase protected E. coli cultures were analyzed under various fermentation conditions in shake flasks and bioreactor. Co-expression of the methylase gene resulted in higher enzyme production rates for longer periods yielding 250x106 U/L Taq I endonuclease activity in crude cellular extracts of E. coli BL21(DE3)[pTaqR, pMETaq] cells.
Keywords: Proteins -- Chemical modification.